The Relationship Between the Role of Posyandu Cadres and Elderly Posyandu Services in the Work Area of the Uptd Health Center - Khoirul Anwar Pulungan; Reni Aprinawaty Sirait; Delita Br. Panjaitan (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The role of Posyandu cadres is crucial in improving the quality of health services for the elderly. The elderly are vulnerable to various health issues and require special attention, especially in areas such as Asahan Regency, where the role of cadres as companions, communicators, and motivators significantly impacts the quality of services. Elderly Posyandu aims to enhance the quality of life for the elderly through integrated health services, but challenges remain in increasing participation and service effectiveness. Research Objectives: This study aims to analyze the relationship between the role of Posyandu cadres and the quality of Posyandu services for the elderly in the working area of UPTD Puskesmas Bandar Pasir Mandoge, Asahan Regency. Research Methods: This research uses a quantitative design with a cross-sectional approach, involving 86 elderly participants selected through accidental sampling. Data were collected using questionnaires and analyzed using Chi-square tests to examine the relationship between the role of cadres and elderly satisfaction with Posyandu services. Results: The analysis shows a significant relationship between the role of Posyandu cadres and service quality. The p-values for the roles of cadres as companions, communicators, and motivators are all 0.000, indicating a significant positive impact on elderly satisfaction with Posyandu services. The better the role of the cadres in accompanying, connecting, and motivating, the higher the satisfaction of the elderly. Conclusion: The role of Posyandu cadres as companions, communicators, and motivators significantly affects the quality of Posyandu services for the elderly. Regular training to improve cadre capacity is essential to enhance the effectiveness of elderly health services in Asahan Regency.